Identifying Concurrency Control from a Sequential Proof - Ramalingam, G.; Rajamani, Sriram; Ranganath, Venkatesh-Prasad; Vaswani, Kapil; Deshmukh, Jyotirmoy Vinay (2008)
The claimed subject matter provides a system and/or a method that facilitates ensuring non-interference between multiple threads that access a shared resource. An interface can receive a portion of sequential code, wherein the portion of sequential code includes a property that is maintained and relied upon when invoked and executed by a sequential client. A synthesizer component can leverage a sequential proof related to the portion of sequential code in order to derive a concurrency control mechanism for a portion of concurrency code that maintains the property when invoked by a concurrent client, wherein the sequential proof identifies a concurrent interference at an execution point that is tolerable for the concurrent client.